Endoscopic Dilatation versus Oesophageal Stent in Benign Oesophageal Stricture - Hadyanto Caputra; Iqbal I Awang; Prionggodigdo Nugroho; Ari Fahrial Syam (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2016)
Aim: Oesophageal stricture is one of the causes of dysphagia. It is a condition in which the lumen of oesophagus is narrowed by fibrotic tissue in the oesophageal wall. It is usually caused by inflammation or any other cause that leads to necrotizing of tissue. It is mainly differentiated into benign or malignant. The aim of this article is to answer the clinical question on the effectiveness of oesophageal stenting compared to endoscopic dilatation in patient with benign oesophageal stricture due to ingestion of corrosive substances, who had undergone several endoscopic dilatations.Method: We conducted search of relevant articles using PubMed search engine to answer the clinical question. Keywords being used during the search process were: ("oesophageal stricture"[All Fields] OR "oesophageal stenosis"[All Fields] AND (("dilatation"[All Fields] AND ("stents"[MeSH Terms] OR "stents"[All Fields] OR "stent"[All Fields]). Results were further converged by adding specific filters, which were full text articles and clinical trial.Results: The chosen article was further appraised in order to identify its validity and eligibility to answer the clinical question. We chose to use CONSORT (statement to improve the quality of reporting of RCTs) to facilitate the critical appraisal and interpretation of RCTs.Conclusion: Stenting was associated with greater dysphagia, co-medication and adverse events. No randomized controlled trials which compared biodegradable stents with other stents or with balloon dilatation was identified. Lack of adequately robust evidence for effectiveness and cost-effectiveness formed the rationale of this trial.